Religious-based family management and its impact on consumption patterns and poverty: A human resource and management perspective - Hasmin Hasmin; Jumiaty Nurung; Gunawan Bata Ilyas (Economies, 2025)
Research Objective: This study aims to examine the impact of religious-based family management (RBFM) on absolute poverty through two main factors: short-term vision and uncontrolled consumption among low-income families. Research Methods and Approach: This study analyzed 172 respondents (low-income families) using a quantitative approach with the Amos Structural Equation Modeling (SEM) method. A questionnaire was the main instrument in this study of six regions in South Sulawesi. Findings and Research Novelty: The findings reveal that, as an 'agent of change', RBFM has a significant negative effect on short-term vision, uncontrolled consumption, and absolute poverty. These results underscore the role of integrating religious values in family management to curb excessive consumption behavior and strengthen long-term financial planning, thereby potentially breaking the cycle of poverty. The novelty of this research lies in employing Human Capital Theory (HCT) and the Theory of Planned Behavior (TPB) to elucidate the role of religion in the economic dynamics of family life. Research Implications: This study provides important implications for poverty alleviation policies, particularly in developing value-based programs that integrate religious principles with financial literacy. Such interventions are expected to enhance financial management practices among low-income families and foster their economic sustainability.
Keywords: 330; religious-based family management; short-term vision; uncontrolled consumption; absolute poverty; human capital theory; theory of planned behavior; Indonesia